A New Year, Newfangled COVID-19 Variant B.1.640.2 (IHU): What We Know So Far? - Ray, Suman K.; Mukherjee, Sukhes (Infectious Disorders - Drug Targets, 2023)
A new COVID-19 variant that no one currently wants has emerged with the start of the new year. Omicron, which was first discovered in November of last year, was only just beginning to be understood when another strain uncovered in France made headlines. On January 4, 2022, news of the variant exploded on social media, but cases of what is now known as variant B.1.640.2 (IHU) were initially discovered about two months prior. Evidence is still being gathered, but internet misinformation regarding the latest coronavirus variety is already rampant, as it was with Omicron. The majority of existing vaccines target SARS-spike CoV-2's protein, which the virus utilizes to enter and infect cells. Epidemiologists and virologists worldwide are concerned about the virus' spike protein, which plays a key role in how your body identifies and reacts to the virus. Spike proteins are produced, recognized, and defended against by our immune system. Your body and the vaccines you have had injected into your system have a far harder time fighting the virus when the amino acids in a protein are altered or removed.
Keywords: IHU